PENERAPAN TEKNIK ROLE PLAYING DALAM BIMBINGAN KELOMPOK TERHADAP PERILAKU PROSOSIAL SISWA DI MASA PANDEMI COVID-19 - Yunia Shinta Dewi; Siti Fatimah; Reza Pahlevi (IKIP Siliwangi, 2021)
This research was motivated by the existence of the Covid-19 pandemic condition which affected the provision of guidance and counseling services in schools, especially the provision of group guidance services to grade VII students at MTs Al-Inayah Bandung City. To support group guidance service activities, interesting techniques are needed so that these services are in demand by students, namely by using role playing techniques, role playing activities between students in groups by playing a real role in everyday life. Grade VII students are a transitional period of developmental tasks from childhood to adolescence. Prosocial behavior is one of the developmental maturities of adolescence, but in reality there are still students who have not optimized this development, in order to prevent misconduct, therefore group guidance services with techniques are needed role playing. This research was conducted using qualitative research methods. The data collected in this study are data obtained through observation, interviews and documentation. The subjects in this study were 3 students who tended to have a less caring attitude towards others, low tolerance and help to help. The results showed that after being provided with services by the counseling teacher, there was a change in behavior that was displayed compared to before being given the service. So it can be understood that the application of group guidance services with techniques is role playing effective on the prosocial behavior of class VII students at MTs Al-Inayah Bandung.Keywords: Group Guidance Service, Role Playing Techniques, Prosocial Behavior